THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF INTEGRATING NON-VERBAL MEANS INTO THE EDUCATIONAL PROCESS - Allanazarova, Feruza Karimberdievna; Xojanazarova, Guljan Bahadirovna (SCIENCE and SOCIETY, 2026)
The article also analyzes the theory of integrating nonverbal means in the educational process. Studies have shown that combining verbal and nonverbal elements increases the level of understanding of information by students, develops interactive activity and is an important tool in achieving pedagogical goals. In order to effectively integrate nonverbal means into the teaching process, the teacher should use eye contact, gestures, pantomime and proxemic elements in a purposeful and systematic manner.
Keywords: speech; nonverbal means; communication; dialogue; facial expressions; gesture; signal; body position; gaze; proxemics; chronemics; paralinguistic means